Leaving Church: Resisting Mormon authority and community in online-offline dimensions - Cheong, Pauline Hope; Fisk, Megan (AoIR Selected Papers of Internet Research, 2013)
Membership in religious organizations often entails dedicated attention to its dogma, moral vision, sacred leadership and community, yet some members ultimately choose to leave. In light of the recent rising and unprecedented number of Mormon church resignations, this paper examines the motivations and experiences of those who choose to leave the church, including the underexamined role of digital and social media in the disaffiliation process. Drawing from turning point analysis, which utilizes the retrospective technique to collect 40 in-depth interviews of ex-Mormons, results will discuss their exit tactics of resistance as well as the extent and ways in which they (re)appropriate traditional and new religious texts, and connect to new networks in their transition.